The Influence of Demonstration Methods on Islamic Religious Education Learning Results in Class II Students at SDN Tegalega II - Saharrani Rezkia Mutiara Soedirman; Jaenal Abidin; Ferianto, Ferianto (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This research consists of two variables, namely the influence of demonstration methods and the learning outcomes of Islamic religious education, thus the aim of this research is to describe the picture of student learning outcomes using demonstration methods, as well as the influence of both in correlational relationships. The population in this study was students at SDN Tegalega II, and the sample was class II students at SDN Tegalega II, Ciampel. The research method used in this research is correlational research with a quantitative approach, this method was chosen to identify the relationship between the influence of demonstration methods on the learning outcomes of Islamic religious education. Data related to the influence of demonstration methods on the learning outcomes of Islamic religious education was collected using a questionnaire instrument, which was prepared using a Likert scale, a data analysis technique using detective and inferential analysis. The results of this study showed that the effect of the demonstration method was 12% in the low category, 72% in the medium category and 16% in the high category. So it can be concluded that the average influence of the demonstration method at SDN Tegalega II is in the medium category. Then the results of studying Islamic religious education were 16% in the low category, 60% in the medium category, 24% in the high category, so it can be concluded that the results of studying Islamic religious education for class II students at SDN Tegalega II are in the medium category. Based on the SPSS outpus in the coefficientsa table, it is known that the significant value (sig) is 0.719 > 0.05 so it can be concluded that HO is accepted and Ha is rejected, which means that “there is no influence of the demonstration method (x) on the learning outcomes of Islamic religious education (y). From the analysis results, it is known that the value R Square = 0.30, thus, it can be concluded that the influence of the demonstration method (x) on the desire to learn Islamic religious education (y) is 30%, while 70% is influenced by other variables that are not variables of this research.